2000
DOI: 10.1182/blood.v96.9.3279
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of organ-related transmission of Kaposi sarcoma–associated herpesvirus or human herpesvirus-8 in transplant patients

Abstract: In transplant patients, Kaposi sarcoma (KS)-associated herpesvirus or human herpesvirus-8 (HHV-8) infection is associated with the development of KS, primary effusion lymphoma and Castleman disease. Whether HHV-8 is either reactivated in the recipient or transmitted by the donor has been investigated so far only by serologic studies. Thus, we addressed the issue of HHV-8 transmission in the transplantation setting by molecular methods. We exploited the high level variability of the orf-K1 gene and the polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…HHV‐8 infection in SOT recipients may occur either as primary infection in HHV‐8 seronegative recipients of allografts from HHV‐8 seropositive donors or as secondary reactivation of latent virus . The incidence of HHV‐8 infection and associated malignancies in SOT recipients is variable depending on the geographic area and it mirrors the varied seroprevalence worldwide .…”
Section: Human Herpesvirusmentioning
confidence: 99%
“…HHV‐8 infection in SOT recipients may occur either as primary infection in HHV‐8 seronegative recipients of allografts from HHV‐8 seropositive donors or as secondary reactivation of latent virus . The incidence of HHV‐8 infection and associated malignancies in SOT recipients is variable depending on the geographic area and it mirrors the varied seroprevalence worldwide .…”
Section: Human Herpesvirusmentioning
confidence: 99%
“…Serology studies also indicated that HHV‐8 transmission occurs through solid organ, for example, kidney or liver, transplantation 10 . Molecular DNA analysis demonstrated HHV‐8 transmission through kidney transplantation 11 . What was not determined in these studies was whether viral transmission occurred through infected cells of the transplanted organ or via infected lymphocytes contained within the organ.…”
mentioning
confidence: 99%
“…On the other hand, the risk of HHV‐8 transmission after organ transplantation is not well known. Organ graft recipients can develop KS when they are infected with HHV‐8, but it is unknown whether this is a result of reactivation of latent HHV‐8 or of HHV‐8 transmission through organ transplantation 16–18 …”
mentioning
confidence: 99%